1998
DOI: 10.1002/(sici)1098-2299(199802)43:2<117::aid-ddr5>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of new soft anticholinergic agents

Abstract: The design and evaluation of two new soft anticholinergic agents, ethoxycarbonylphenylcyclopentylacetyl-N,N-dimethyltropinium methyl sulfate (PCMS-1) and methoxycarbonylphenylcyclopentylacetyl-N,N-dimethyltropinium methyl sulfate (PCMS-2) are presented. According to the inactive metabolite approach of the soft drug design and using methatropine as the lead compound, the corresponding ethyl-and methylesters were formed and a cyclopentyl ring was also introduced in the structures. By the latter, the enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Hence, it represents a size and shape descriptor, as it depends on the shape of the molecule and, for common organic molecules, it also scales with size. Our previous 2 structureactivity relationship studies already indicated an important role played by molecular size in this class of soft anticholinergics (9,53). In the present study, molecular size as measured, for example, by volume is still highly correlated with muscarinic binding activity in the analyzed 3 receptor subtypes; however, ovality (O e ) seems to be somewhat more relevant.…”
Section: Quantitative Structure-activity Relationships (Qsars)supporting
confidence: 44%
See 3 more Smart Citations
“…Hence, it represents a size and shape descriptor, as it depends on the shape of the molecule and, for common organic molecules, it also scales with size. Our previous 2 structureactivity relationship studies already indicated an important role played by molecular size in this class of soft anticholinergics (9,53). In the present study, molecular size as measured, for example, by volume is still highly correlated with muscarinic binding activity in the analyzed 3 receptor subtypes; however, ovality (O e ) seems to be somewhat more relevant.…”
Section: Quantitative Structure-activity Relationships (Qsars)supporting
confidence: 44%
“…On the basis of previous studies (9,10), the most labile soft anticholinergics from each series of soft anticholinergics were chosen to test the integrity of the compound during incubation with the esterase enzyme inhibitor. AQC, PMTR.Et, PCMS-1, PCDT, and PCTM were chosen to test the stability in the receptor media.…”
Section: Stability Studies Of Soft Anticholinergics In the Receptor Ementioning
confidence: 99%
See 2 more Smart Citations
“…65 This compound was shorter acting than even tropicamide, and, consistent with the soft drug approach, the untreated eye did not show any mydriasis, as opposed to administration of methscopolamine. Other structures like the cyclopentyl derivative 16 (PCMS-2) 64 or different phenylsuccinic analogues of methatropine 63 and methscopolamine 66 were also investigated. As recently shown, 16 was equipotent to atropine in protecting against carbachol-induced bradycardia in rats, but the duration of action was again significantly shorter (15-30 min vs. more than 2 h) ( Fig.…”
Section: Soft Anticholinergics IImentioning
confidence: 99%